Children's Views and Experiences of Treatment Adherence and Parent/Child Co-Management in Eczema: A Qualitative Study - Emma Teasdale; Katy Sivyer; Ingrid Muller; Daniela Ghio; Amanda Roberts; Sandra Lawton; Miriam Santer (MDPI AG, 2021)
Eczema affects one in five children and can have a substantial impact on quality of life. This qualitative study aimed to explore children's views and experiences of eczema and what may affect treatment adherence from their perspective. We conducted semi-structured, face-to-face interviews with children with eczema aged 6-12 years from March to July 2018. Interviews were transcribed verbatim and analysed using inductive thematic analysis. We found that children do not typically view eczema as a long-term condition, and topical treatments (predominately emollients) were seen to provide effective symptom relief. Uncertainty around co-managing at home was expressed as children typically felt that parental reminders and assistance with applying different types of topical treatments were still needed. For some children, eczema can be difficult to manage at school due to a lack of convenient access and appropriate spaces to apply creams and psychosocial consequences such as attracting unwanted attention from peers and feeling self-conscious. Treatment adherence could be supported by reinforcing that eczema is a long-term episodic condition, providing clear information about regular emollient use, practical advice such as setting reminders to support co-management at home, and working with schools to facilitate topical treatment use when necessary.